Pengaruh Motivasi Kerja Dan Disiplin Kerja Terhadap Kinerja Perawat Pada RSIA Tiara Fatrin Palembang - Rima Rima; Siti Komariah Hildayanti; Try Wulandari (Training & Research Institute - Jeramba Ilmu Sukses, 2023)
A hospital is an institution that provides medical services and is responsible for providing treatment, treatment, and efforts for healing and health for patients, as well as organizing healthy living education in the community. The purpose of this study was to find out whether there was an influence of work motivation and work discipline on the performance of nurses at RSIA Tiara Fatrin Palembang. In this study, the object studied was nurses at the Tiara Fatrin Mother and Child Hospital in Palembang, totaling 50 people and different characteristics including 38 women and 12 men. This study used a saturated sampling technique. Based on the results of the tests that have been carried out, it is known that in the simultaneous test results (F) the variables of work motivation and work discipline on the performance of nurses have a positive and significant effect with a calculated F value obtained of 78.518 while the table F value is 3.20 with a significant level of 0.000 0.05. Based on the results of the analysis of the R2 determination variables for variables X1 and X2, it has a positive and significant effect on Y at RSIA Tiara Fatrin Palembang, this can be proven based on table 4.12 R Square values of 0.770 or 77%. It can be concluded that the variables X1 and X2 affect the variable Y.